What Can Unions Do? An Impact Estimate for an Increase in the US Private-Sector Unionization Rate on Workers' Earnings. Issue 3 (August 2023) - Kristal, Tali
Unions are known to increase earnings and wage equality. Therefore, indications for recent union revitalization provoke the question of what unions would do today were they to restore their union density and hence power to the level of the early 1980s (about 20%). This article presents wage estimates for 1983 to 2020, assuming a 20% union density from 1983 onward, revealing higher earnings and lower wage inequality. However, since union membership today typifies low-wage workers with weaker bargaining power than formerly, the benefits from restoring union density and power will likely be lower today than in the past.